2020
DOI: 10.3390/cells9020456
|View full text |Cite
|
Sign up to set email alerts
|

α2-Adrenergic Receptor in Liver Fibrosis: Implications for the Adrenoblocker Mesedin

Abstract: The noradrenergic system is proposed to play a prominent role in the pathogenesis of liver fibrosis. While α1- and β-adrenergic receptors (ARs) are suggested to be involved in a multitude of profibrogenic actions, little is known about α2-AR-mediated effects and their expression pattern during liver fibrosis and cirrhosis. We explored the expression of α2-AR in two models of experimental liver fibrosis. We further evaluated the capacity of the α2-AR blocker mesedin to deactivate hepatic stellate cells (HSCs) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Furthermore, the expression of α 2Α -AR was significantly upregulated in the lungs of septic mice. Other studies have demonstrated that inhibiting the α 2 -AR receptor could reduce fibrosis in the liver and kidney (12,13). Similar to these findings, we observed that the α 2 -AR antagonist YHB ameliorated sepsis-mediated pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the expression of α 2Α -AR was significantly upregulated in the lungs of septic mice. Other studies have demonstrated that inhibiting the α 2 -AR receptor could reduce fibrosis in the liver and kidney (12,13). Similar to these findings, we observed that the α 2 -AR antagonist YHB ameliorated sepsis-mediated pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…43 Hepatic fibrogenesis is characterized by increased and altered deposition of ECM and represents the most common and pathogenic hallmark of CLD. Although several other cell types may also participate in the onset and development of liver fibrosis, hepatic stellate cells (HSC) are recognized as the primary cells responsible for ECM deposition, and are responsive to neural inputs, 10,44 suggesting a likely contributive if not causal impact of AGCs on the activation of HSCs, perhaps both ways.…”
Section: A Xon G U Idan Ce Molecule S In Cldmentioning
confidence: 99%
“…Moreover, clinically more importantly, it is likely that efforts to lower its accumulation in the brain could have adverse effects on the liver [51]. The same group investigated aspects of α 2 -adrenergic receptor signaling [52]. This receptor system consists of three homologous subtypes (α 2A , α 2B , α 2C ) and has important roles in catecholamine signaling in different structures of the central nervous system.…”
Section: Communication Among Organs In Pathogenesis Of Hepatic Fibrosismentioning
confidence: 99%
“…This receptor system consists of three homologous subtypes (α 2A , α 2B , α 2C ) and has important roles in catecholamine signaling in different structures of the central nervous system. Interestingly, the different subtypes showed differential expression in carbon tetrachloride or bile duct-ligated mice, while the α 2 -adrenoblocker mesedin reduced profibrogenic markers and α 2A expression in culture murine HSC [52]. Moreover, mesedin enhanced expression of eNOS and suppressed TGF-β expression in a human hepatic sinusoidal endothelial cell suggesting α 2 -adrenergic receptor system to contribute to liver fibrosis by alleviating HSC activation and increasing the permeability of liver sinusoids during liver injury [52].…”
Section: Communication Among Organs In Pathogenesis Of Hepatic Fibrosismentioning
confidence: 99%